Globe of Revolution. An Afterthought on Geophilosophical Realism - Negarestani, Reza (Identities: Journal for Politics, Gender and Culture, 2011)
Author(s): Reza Negarestani Title (English): Globe of Revolution. An Afterthought on Geophilosophical Realism Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 2 (Summer 2011) Publisher: Department of Gender Studies, Euro-Balkan Institute Page Range: 25-54 Page Count: 29 Citation (English): Reza Negarestani, “Globe of Revolution. An Afterthought on Geophilosophical Realism,” Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 2 (Summer 2011): 25-54.